Distributed heterogeneous energy storage systems synchronization control with dynamic weights and time-varying unbalanced digraphs. (December 2020) - Kang, Wenfa; Chen, Minyou; Lai, Wei; Wu, Kunming; Cheng, Tingli
Abstract: This paper provides a distributed control strategy for battery energy storage systems (BESS) based on multi-agent system. The proposed control laws can guarantee that the state of charge (SoC) is synchronized, and BESS active power can be shared proportionally. Moreover, the heterogeneous characteristics of BESS are considered in modeling BESS and designing control laws, while they are not carefully considered in the existed literature. Besides, the proposed control laws are robust to the changing communication topologies and link broken since they can be applied over the time-varying directed unbalanced communication networks. Simulation studies, which are carried out on matlab/simulink, validate the effectiveness of the control strategy and laws.